Narrative: problems and promises of an alternative paradigm / Narrativa: problemas e promessas de um paradigma alternativo - Jens Brockmeier; Rom Harré (Psicologia: Reflexão e Crítica, 2003)
The increasing interest in the study of narrative and its social contexts suggests the emergence of another strand to the post-positivist paradigm and a further refinement of interpretive methodology in the human sciences. The problem of accounting for the dynamic patterns of human behavior seems to be nearer to a solution through studies of narrative even than through such well-known approaches as the use of the role-rule model or script theory. In this paper we will look at some of the qualities that have made the study of narrative such a productive approach. In doing so, we shall define the notion of narrative and differentiate it from other patterns of discourse, drawing on socio- and psycholinguistics as well as on literary and philosophical studies. A second concern will be to identify some theoretical difficulties and possible dangers of which, we believe, students of narrative should be aware. Finally, we will outline an understanding of narrative that aims to take into account its particular discursive embeddedness and its transitory character.